MAKSIMALISASI EVALUASI PENDIDIKAN AGAMA ISLAM - Ade Idham Prayogi (AL-ASASIYYA: Journal Of Basic Education, 2017)
Assessment becomes a very important part and parcel of teaching and learning activities. If learning has an important role in supporting the development of religious students, then the evaluation functions as a provider of information to know the success rate of the teaching and learning process is running. Without the presence of evaluation activities, there may be found information on the shortcomings and advantages of teaching and learning activities that have been implemented. Practically, the attitude and action are also not might be taken.  The evaluation sought to determine whether the educational objectives are achieved or not, so the evaluation has no small role in Islamic studies if carried out properly.